Laws of the (Is)lands: Comparing the law codes of Iceland and Gotland during the long fourteenth century - Gaines, Gregory Callahan, 1993- (2018)
This project explores the connection between the islands of Iceland and Gotland during the ‘long’ fourteenth century (roughly 1260-1407) through their respective law codes. Jónsbók and the Gutalag were both codified around a similar time period. They share many similarities, particularly in their handling of crime and punishment, inheritance, tithe and taxes, the Church, and domestic laws related to horses and ships. The islands themselves have many intangible similarities which have yet to be examined academically, but by applying an evolutionary biology framework to the subject of legal history, this project points out very tangible links in the islands’ medieval laws. The sources for this project are primarily translations, diplomatic editions, and photographs of the legal codes. In addition to these main texts, other research on relevant historical matters pertaining to Scandinavia during the fourteenth century is included. By working directly with the translated texts, in concert with original language versions, the project shines light on law codes that are fairly understudied and deserving of more research. Both Jónsbók and the Gutalag have been somewhat neglected in English language legal history, and a comparison of the two laws serves a dual purpose of providing more insight into the laws themselves and comparing the legal cultures of the islands. The overall aim of the project is to establish a connection between Gotland and Iceland through one facet of their medieval histories. In short, the project seeks to answer the question ‘What are the similarities between the legal histories of Gotland and Iceland during the long fourteenth century?’ Þetta verkefni skoðar tengsl eyjanna Íslands og Gotlands á „löngu fjórtánda öldinni “(u.þ.b. 1260-1407) með samanburði á lögbókum eyjanna tveggja. Jónsbók og Gutalagen sem voru ritaðar um svipað leiti. Þær eiga margt sameiginlegt, einkum í meðhöndlun á glæp og refsingu, erfðarétti, tíund og sköttum, málefnum kirkjunnar og lögum sem tengjast hestum og skipum. ...